Analysis and Management of the content of tourist information in digital media of the General Villamil Playas canton - León Ramírez, Fernando; Fajardo Chalén, Solange; Polet Dick Zambrano, Natalia (Historia y Comunicación Social, 2021)
The purpose of this project aims to analyze the content of tourist information and how the digital media is currently managed in the beaches of General Villamil Playas. This place is the most visited for both local and international tourists is the Cantonal Head as it counts with infrastructure and basic services in all aspects: it has a wide gastronomic variety and includes the principal beaches of the canton such as Playa Humboldt, Playa Paraíso, Puerto of Engabao. There are other natural attractions in the surroundings of the Cantonal Head, which are not recognized because the lack of promotion in the digital media as well a good analysis & management of the public and private digital marketing. This project looks forward to implement the proposal where the inhabitants of the canton obtain benefits for socio-economic growth and tourists be interested about visiting the canton. In order for this to happen, the involvement of the public sector is important, to implement digital media with current, verified information that can interact with the people interested, so that both, national and foreign tourists wish to visit the canton.
Keywords: Digital media; tourist promotion; tourist attractions; ignorance